Synthesis and Dimerization Behavior of Five Metallophthalocyanines in Different Solvents - Zhenhua Cheng; Na Cui; Hongxiao Zhang; Lijun Zhu; Daohong Xia (Advances in Materials Science and Engineering)
Metallophthalocyanine (MPc) has become one of the metal organic compounds with the largest production and the most widely application, because of its excellent performance in catalytic oxidation. However, aggregation of the MPc in solution, resulting in decreased solubility, greatly limits the performance of application. Studying the behavior of dimerization of MPcs can provide a theoretical basis for solving the problem of the low solubility. So five metallophthalocyanines (FePc, CoPc, NiPc, CuPc, and ZnPc) were prepared with improved method and characterized. Dimerization of the five MPcs was measured by UV-Vis spectroscopy separately in N,N-dimethyl formamide (DMF) and dimethylsulfoxide (DMSO). The red-shift of maximum absorption wavelength and deviations from Lambert-Beer law with increasing the concentration were observed for all the five MPcs. The dimerization equilibrium constants (K) of the five MPcs in DMF were arranged in order of CoPc > ZnPc > CuPc > FePc > NiPc, while in DMSO they were arranged in order of ZnPc > CoPc > FePc > CuPc > NiPc. The type of the central metal and nature of the solvent affect the dimerization of the MPcs.